(untitled) (European Journal of Pure and Applied Mathematics, 2023)
Let F be a real valued generalized biaxisymmetric potential (GBASP) in L^β on S_R, the open sphere of radius R about the origin. In this paper we have obtained the necessary and sufficient conditions on the rate of decrease of a sequence of best harmonic polynomial approximates to F such that F is harmonically continues as an entire function GBASP and determine their (p,q)-order and generalized (p,q)-type with respect to proximate order ρ(r).